The Transformation of Institutional PR in Bulgaria - Velichkova, Svetozara (Проблеми на постмодерността, 2025)
The article is an attempt to analyze the change in the communication paradigm of modern society and how institutional PR practitioners in Bulgaria can effectively communicate through social networks with their audiences. The scientific research methods used are general scientific methods - logical analysis and synthesis, induction, deduction, and observation. The article aims to present the advantages of online communication tools, which are already part of the activities of institutional PR practitioners. The conclusions are that due to the advantages that Web 2.0 communication provides through social networks, institutional PR practitioners in Bulgaria are increasingly starting to use this PR tool in their activities. The article shows that digital PR tools can be effective for PR practice in Bulgaria. It is concluded that institutional PR practitioners must acquire new skills to implement effective digital communication, especially those working in state institutions. They must not only acquire skills but also use the advantages of digital PR tools. For them, improving the communication of institutions with the public should be an important priority.